Exploring the Applications and Challenges of ChatGPT in Research and Academia: A Comprehensive Review - Nepal, Tej Kumar (Westscience Press, 2024)
The fast advancement of artificial intelligence (AI) technology in recent years has profoundly impacted the academic and research landscape. Among these developments, OpenAI’s ChatGPT, a cutting-edge language model, has been a game-changer for natural language creation and processing. This research review thoroughly investigates the various uses and difficulties related to incorporating ChatGPT into the domains of academia and research. ChatGPT is a flexible language model that shows promise across multiple research fields, from text summarization and language translation to supporting the automation of literature reviews. The review aims to objectively evaluate ChatGPT’s impact on academic writing processes by examining how it contributes to draft creation, writing assistance, and manuscript improvement. Furthermore, the effect of the model on education is reviewed, exploring its possible contributions to personalized education, intelligent tutoring systems, and language learning help. Though the assessment highlights the need for responsible deployment, it also discusses ethical issues, potential biases, and inherent limitations in its promising uses. This research review paves the path for future innovations and informed usage of ChatGPT within academic and research contexts by combining insights into the advantages and problems of the platform. It also provides a comprehensive awareness of the existing landscape.